Death in the floating city - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2012)
Entreated for help by a childhood nemesis who has been wrongly accused of murder, Lady Emily launches an investigation in Venice that takes her from elegant palazzi to slums, libraries, and bordellos before she links the crime to a centuries-old puzzle.